Bipolar and fixable probe targeting mitochondria to trace local depolarization via two-photon fluorescence lifetime imaging1. Issue 16 (21st August 2015) - Wang, Benlei; Zhang, Xinfu; Wang, Chao; Chen, Lingcheng; Xiao, Yi; Pang, Yi
<x xml:space="preserve">Abstract</x> A two-photon probe MITFPS maintains permanent localization in inner mitochondrial membranes through chemical immobilization and assembly into the phospholipid layer, which enables exclusive signaling of mitochondrial delocalization.